Distinguishing the impacts of ozone‐depleting substances and well‐mixed greenhouse gases on Arctic stratospheric ozone and temperature trends. Issue 7 (11th April 2014) - Rieder, Harald E.; Polvani, Lorenzo M.; Solomon, Susan
Abstract: Whether stratospheric cooling due to increases in well‐mixed greenhouse gases (WMGHG) could increase the depletion of Arctic stratospheric ozone has been the subject of scientific and public attention for decades. Here we provide evidence that changes in the concentrations of ozone‐depleting substances (ODS), not WMGHG, have been the primary driver of observed Arctic lower stratospheric trends in both ozone and temperature. We do so by analyzing polar cap ozone and temperature trends in reanalysis data: these clearly suggest that both trends are mainly driven by ODS in the lower stratosphere. This observation‐based finding is supported by results from a stratosphere‐resolving chemistry‐climate model driven with time‐varying ODS and WMGHG, specified in isolation and in combination. Taken together, these results provide strong evidence that ODS are the main driver of changes in the Arctic lower stratospheric temperatures and ozone, whereas WMGHG are the primary driver of changes in the upper stratosphere. Key Points: Polar cap mean temperature is a better proxy for Arctic ozone than VPSC Observations and models show that ODS have driven ozone and temperature trends In coming decades increasing greenhouse gases will play a bigger role